PROFIL PAKAN DAN KONSUMSI HIJAUAN PAKAN TERNAK KAMBING PERANAKAN ETAWA (Studi Kasus Di Peternak Rakyat Dusun Prodo Desa Klampok Kecamatan Singosari, Kabupaten Malang) - Usvinit, Finsensiana; Marhaeniyanto, Eko; Darmawan, Hariadi (Universitas Tribhuwana Tunggadewi, 2018)
The purpose of this research is to know feed profile and forage consumption on goats of Peranakan Etawa. The benefits of this study are expected to provide information on the evaluation of the type of forage feed given as goat feed. This research was conducted in Prodo Village, Klampok Village, Singosari Sub-district, Malang Regency, East Java on 1st February 2017 to 2nd March 2017.Object in this research is goat farmer as respondent counted 50 people with criteria that have goat herd, number of ownership of goats ? 2 heads, long breeding ? 5 years. Number of livestock observed as many as 65 goats (adult 33 heads, young 22 heads and till 10 heads). The method used is case study with descriptive data presentation. Primary data collection was obtained from respondents using questionnaires, interviews, observation and documentation. Secondary data are documents of village government, books, library materials, and literature. Sampling by purposive sampling. The variables observed were frequency and amount of forage feed, consuption of forage feed. The results of this studyshowed that most animal feed given to goast is paitan, grassy field, and kaliandra, The consumption of forage for goat feed at researchlocation of dry matter consumption value BK / ST livestock unit (ST) is 12,92 kg / ST equal to 3,9% from body weight. Tujuan penelitian untuk mengetahui profil pakan dan konsumsi hijauan pada ternak kambing Peranakan Etawa. Penelitian dilaksanakan di Dusun Prodo, Desa Klampok Kecamatan Singosari Kabupaten Malang, Jawa Timur mulai tanggal 1 Pebruari 2017 sampai 2 Maret 2017. Materi penelitian adalah peternak kambing sebanyak 50 orang, dengan kriteria peternak memiliki ternak kambing ? 2 ekor, lama beternak ? 5 tahun. Jumlah ternak yang diamati sebanyak 65 ekor kambing ( dewasa 33 ekor, muda 22 ekor, dan anakan 10 ekor). Metode yang digunakan studi kasus dengan penyajian data secara deskriptif. Data primer diperoleh dari responden menggunakan teknik kuesioner, wawancara, observasi dan dokumentasi. Data sekunder dari data dokumen pemerintah Desa, buku, bahan pustaka, dan literature. Pengambilan sampel secara purposive sampling. Variabel yang diamati adalah frekuensi dan jumlah pemberian pakan hijauan, konsumsi pakan hijauan. Hasil penelitian menunjukan pakan ternak yang paling banyak diberikan kepada kambing adalah paitan, rumput lapang, dan kaliandra. Konsumsi hijauan pakan ternak kambing nilai bahan kering (BK)/satuan ternak (ST) adalah 12,92 kg/ST setara dengan 3,9% dari bobot badan.